First children's dictionary - Greenwood,Marie (London Dorling Kindersley, 2016)
With over 3,000 entries of updated, curriculum-linked content, First Children's Dictionary is an ideal starting place for young children wanting to describe the world around them. From using a dictionary to word histories that help develop an understanding of where words come from, this dictionary for kids is an essential first reference book